PENERAPAN MODEL PEMBELAJARAN PROBLEM BASED LEARNING (PBL) BERBANTUAN MEDIA ANIMASI UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS XI SMAN 10 KENDARI PADA MATERI LARUTAN ELEKTROLIT DAN NON ELEKTROLIT - Elya Satri Purnama; Aceng Haetami; Dahlan (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This research was motivated by the low chemistry learning outcomes of eleventh-grade students at SMAN 10 Kendari in electrolyte and non-electrolyte solution topics, which is caused by the abstract characteristics of the material at the submicroscopic level. This study aimed to: (1) describe the learning outcomes of students taught using the Problem-Based Learning (PBL) model assisted by animation media and those taught via PBL without animation media; (2) determine whether there is a significant difference in learning outcomes between the two groups; and (3) describe students' responses toward the implementation of the PBL model assisted by animation media. The research method employed was a quasi-experimental approach with a Non-equivalent Control Group Design. The research population involved all eleventh-grade students at SMAN 10 Kendari, with the sample consisting of the Experiment class (23 students) using the PBL model assisted by animation media and the Control class (25 students) utilizing the PBL model without animation media. The data collection instruments included a 20-item multiple-choice objective test and a student response questionnaire. Data analysis techniques utilized descriptive statistics and non-parametric inferential statistics via the Mann-Whitney U test since the data distribution was non-normal and non-homogeneous. The results showed that: (1) the average post-test score of the experiment class reached 93.47 with a Normalized Gain (N-Gain) increase of 0.56 (Moderately Effective category), while the control class obtained a post-test average of 87.60 with an N-Gain of 0.43 (Less Effective category); (2) there was a significant difference in learning outcomes between the experiment class and the control class based on the Mann-Whitney U test results with an Asymp. Sig. (2-tailed) value of 0.012 < 0.05; (3) students' responses to the implementation of the PBL model assisted by animation media reached an average percentage of 91.08%, falling into the "Very Good" category. In conclusion, the integration of the PBL model with animation media is effective in visualizing abstract chemistry concepts, thereby significantly improving student learning outcomes.